Anisotropic flexible stress sensors based on Loofah/CN/MWCNTs - 刘璐; 贾晓丽; 黄书童; 张景龙; 李守宝; 柯燎亮 (工程科学与技术)
Flexible stress sensors are key components for realizing intelligent perception of robots and autonomous human-machine interaction. In view of the urgent need for high-performance flexible stress sensors with high sensitivity, wide range, and short response time in the field of human-machine interaction, a flexible stress sensor with conductive anisotropy is proposed, which is made of natural porous loofah as the matrix material and carbon nanoparticles/multi-walled carbon nanotubes (CN/MWCNTs) multidimensional composite materials as conductive coatings. The influence of electrode arrangement on the sensitivity of the sensor is discussed. Experimental results show that the sensor sensitivities are 3.63 kPa-1, 6.89 kPa-1, and 2.78 kPa-1 in the stress ranges of 0~15 kPa, 15~35 kPa, and 35~70 kPa, respectively. At the same time, the sensor has a low detection limit of 0.26 N (6.5 Pa) and a fast response/recovery time of 48 ms/80 ms. The amplitude and waveform of the output curve remain well consistent after 10,000+ cycles of loading under 40 kPa stress, which proves the good performance of the sensor. Finally, the practical applications of the sensor in areas such as encrypted communications and human joint motion detection were also demonstrated, indicating its potential applications in multi-dimensional wearable electronics and intelligent robots. ObjectiveAnisotropic flexible stress sensors are key components for achieving intelligent perception in robotics and autonomous human-machine interaction. This paper proposed a Loofah/CN/MWCNTs flexible stress sensor with anisotropic high sensitivity and a wide measurement range. The sensor was composed of a natural porous loofah framework and a multidimensional CN/MWCNTs composite coating. The multidimensional composite mechanism of the CN/MWCNTs coating effectively enhanced the sensor's sensitivity. Furthermore, the loofah-based substrate material, consisting of cellulose and lignin, made the sensor lighter in weight. The use of loofah, which can degrade naturally in the environment, reduced environmental pollution. MethodsThe loofah, after being cleaned and dried, was radially pre-compressed and cut into squares with a side length of 2 cm. It was then immersed in deionized water for 30 minutes at room temperature to enhance its hydrophilicity. To investigate the effects of MWCNTs concentration, CN concentration, and impregnation times on the electrical conductivity of the sensor, an L9(3³) orthogonal experiment was designed with these three factors as variables. MWCNTs and polyvinylpyrrolidone (PVP) were mixed at a ratio of 10:1. PVP was first dissolved in deionized water with thorough stirring, followed by the gradual addition of MWCNTs and CN in small portions with continuous stirring. The resulting suspension was ultrasonically dispersed for 30 minutes using a cell disruptor to ensure uniform distribution of the nanomaterials. Nine groups of MWCNTs/CN suspensions, each with a volume of 500 ml, were prepared according to the compositions listed in Table 2. Figure 2 illustrates the preparation of Loofah/CN/MWCNTs composites through a simple dipping-drying method. The pretreated loofah was immersed in each suspension for 30 minutes and then dried in a constant-temperature oven at 60°C for 30 minutes. Between each step, the samples were rinsed with deionized water to thoroughly remove unbound MWCNTs and CN. The flexible stress sensor was fabricated by attaching copper electrode sheets to the prepared composite material. Four electrode configurations were designed: axial on the same side (AI), axial on opposite sides (AC), circumferential on the same side (CI), and circumferential on opposite sides (CC). The sensing properties of the composite materials were characterized using a digital multimeter and a universal testing machine.The CI sensor exhibited the highest sensitivity, with circumferentially arranged electrodes showing greater sensitivity than axially arranged electrodes, and electrodes arranged on the same side demonstrating higher sensitivity than those arranged on opposite sides. The sensor's sensitivity was 3.63 kPa⁻¹ in the range of 0 to 15 kPa, 6.89 kPa⁻¹ in the range of 15 to 35 kPa, and 2.78 kPa⁻¹ in the range of 35 to 70 kPa. The sensor also demonstrated good environmental stability and negligible frequency dependence. The hysteresis error was calculated to be 11.33%, meeting practical application requirements. Additionally, the minimum detection force and response time were identified as critical parameters for stress sensors. Experimental results indicated a minimum detection force of approximately 0.26N (6.5 Pa). The response time was approximately 48ms, and the recovery time was about 80ms, indicating a rapid response characteristic. Durability was another key performance metric. After more than 10,000 loading cycles at 40 kPa, the sensor's output amplitude and waveform remained consistent. Furthermore, no significant detachment of the nanoconductive materials from the sensor surface was observed after 3,000 cycles, demonstrating that CN and MWCNTs were tightly bonded to the loofah substrate after drying. The measurement error among sensors made from different loofah samples was relatively small, all below 8.35%, indicating good uniformity. These findings further confirmed the excellent reliability and stability of the sensor, establishing a strong foundation for its application in electronic skins, wearable pressure detection devices, and related fields.To investigate the mechanical characteristics of the sensor's strain response, a series of dynamic compression/recovery response tests were conducted. Due to the natural three-dimensional structure of the sensor, composed of cellulose and lignin in loofah, the sensor was able to return to nearly its original state after pressure removal, ensuring excellent mechanical performance under repeated compression and recovery cycles. The irregular, porous loofah exhibited unique mechanical strength, flexibility, and toughness, allowing it to respond to various mechanical pressures. Compression of the pores within the sensor reduced the distance between conductive materials, leading to a decrease in resistance. When the pressure was released, the resistance returned to its initial value. Consequently, the loofah skeleton and conductive coating were compressed and released simultaneously, effectively functioning as a variable resistor. As applied stress increased, the loofah framework became more compact, gradually increasing the contact area between carbon-based materials of different sizes, thereby generating new current pathways. Importantly, as the compactness of the conductive network increased, CN effectively connected MWCNTs, providing additional electron transport pathways. Thus, the sensor detected external pressure by optimizing contact resistance, likely due to the varying number of contact points among multidimensional carbon materials as the loofah structure deformed. ConclusionsA flexible stress sensor with anisotropic conductivity was fabricated using a simple dipping and drying method. The sensor utilized natural porous loofah as the substrate material and CN/MWCNTs multidimensional composites as the conductive coating. An orthogonal experiment was designed to determine the optimal parameters for CN concentration, MWCNTs concentration, and dipping times. The effects of different electrode configurations on the sensor’s sensitivity were also discussed. Experimental results indicated that the sensor developed in this study exhibited a wide measurement range of up to 70 kPa and a sensitivity of 6.89 kPa⁻¹. Compared to recently reported sensors using loofah as the base material, the sensitivity was improved by 77.77 times. Additionally, the sensor demonstrated a low detection limit of 0.26 N (6.5 Pa), a rapid response/recovery time of 48ms/80ms, and excellent durability, maintaining consistent output amplitude and waveform after more than 10,000 loading cycles under 40 kPa stress, confirming its superior performance. The flexible stress sensor successfully generated Morse code signals and enabled real-time detection of human joint movements, indicating its potential applications in encrypted communication and medical rehabilitation. The findings of this study provide valuable guidance and reference for future design and application of flexible stress sensors.